2006
DOI: 10.1037/h0087272
|View full text |Cite
|
Sign up to set email alerts
|

Generalized self-efficacy, self-esteem, and negative affect.

Abstract: In order to help resolve the ongoing debate about the relationship between and the functions of self-esteem and generalized self-efficacy (GSE), the authors tested the hypotheses that GSE predicts future self-esteem and that self-esteem predicts unique incremental variance in future negative affect. Measures of these three constructs were administered to two samples of undergraduates (N = 160 and N = 75) twice over five-six weeks. Time 1 GSE accounted for significant variance in Time 2 self-esteem in both stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 62 publications
4
38
0
1
Order By: Relevance
“…Total scores ranged from 10 to 50, with higher scores indicating greater personal self-esteem. For college student samples, coefficient alphas for RSES were .87-.89 (Lightsey, Burke, Ervin, Henderson, & Yee, 2006;Roberts et al, 1996) in the previous research and .88 in the present study. Construct validity evidence was supported by the negative association between self-esteem and negative affect (Lightsey et al).…”
Section: Methodsmentioning
confidence: 77%
“…Total scores ranged from 10 to 50, with higher scores indicating greater personal self-esteem. For college student samples, coefficient alphas for RSES were .87-.89 (Lightsey, Burke, Ervin, Henderson, & Yee, 2006;Roberts et al, 1996) in the previous research and .88 in the present study. Construct validity evidence was supported by the negative association between self-esteem and negative affect (Lightsey et al).…”
Section: Methodsmentioning
confidence: 77%
“…For example, using a longitudinal design, Lightsey et al (2006) showed that generalized self-efficacy shapes self-esteem but not vice versa, supporting the earlier findings of Smith (1989) and Chen et al (2004). Lightsey et al claimed that their results ran counter to CSE theory because the traits are separate constructs with discrete antecedents.…”
Section: Do the Cse Traits Have Different Antecedents?mentioning
confidence: 78%
“…As such, we are hesitant to conclude at this time that self-esteem should be removed as a CSE trait. Instead, we encourage further research that more directly examines possible causal effects that self-esteem has on work outcomes, which researchers have begun to do (e.g., Lightsey et al, 2006). However, if self-esteem is found to have little impact on self-regulatory functioning, then its removal may be warranted.…”
Section: Self-esteemmentioning
confidence: 89%
See 1 more Smart Citation
“…Finally, to get a more comprehensive view of the psychophysiological concomitants of self-esteem in everyday life, we also assessed negative affect (NA). NA and emotional instability have been found to be negatively associated with self-esteem in a number of studies (e.g., Judge et al, 2002;Lightsey et al, 2006;Lorr and Wunderlich, 1988;Neiss et al, 2005;Richter and Ridout, 2011), although this relationship has not yet been explored in a daily-life setting.…”
Section: Aim Of the Studymentioning
confidence: 95%